Knowledge Documentation Based on Automatic Identification and Clustering of Change Intentions in CAD Data of Wiring Harnesses. (May 2022) - Eder, K.; Herzog, W.; Altner, M. M.; Tas, O.; Neckenich, J.; Paetzold, K.
Abstract: High amount of changes and increasing complexity in CAD design of wiring harnesses result in a lack of time for documentation and transfer of acquired knowledge. To be able to transfer the gained knowledge efficiently during development automating the identification, analyzation and documentation of changes is necessary. This paper shows a methodology to address this challenge for CAD data of wiring harnesses. Thus, it is shown how interrelated change elements can be combined or separated from each other according to their change intention.